What Counts as Qualitative Research? Some Cautionary Comments - Silverman, David (Qualitative Sociology Review, 2013)
Many PhD students begin as unconscious Naturalists or Emotionalists using interview studies to report people’s “experience” of an unquestioned social “problem.” An analysis of articles in one journal shows that this naïve use of interview data has become the common currency of qualitative research. In a critique of one such article, I show how interview studies may simply reproduce interviewees’ own accounts, glossed over by a few social science categories. By “mining” interviews for apposite extracts, such researchers lose sight of how sequence is consequential for what we say and do. Much more needs to be done if qualitative research is not to be just a set of techniques but an analytic project, different from journalism.